The Postdischarge Office Visit: The Critical Role of the Receiving Provider in the Care Transitions Process - Ugochi Ohuabunwa; Jonathan Flacker (Association of American Medical Colleges, 2014)
Abstract Introduction The transfer of patient care from the hospital team to healthcare providers in the community is a high-risk process characterized by fragmented, non-standardized care. The contributory role of provider-related factors to failure in transitions of care is becoming more prevalent with the emerging phenomenon of variable care providers in the inpatient and outpatient setting, potentially resulting in discontinuity of care. As a result, there is an increasing need for trainees to understand the crucial roles of promoting safety during transitions of care between providers that both send and receive patients. This resource is aimed at educating students on the critical role of the receiving outpatient physician/ interprofessional team in care coordination and safety promotion during care transitions. Methods The activities are delivered in the context of an interactive case-based learning workshop. The workshop incorporates activities that simulate a patient's postdischarge office visit with participants acting as the patient's primary care physician. During this activity, the learners are trained to structure the postdischarge visit, and identify both the patients' postdischarge care needs and factors that present a risk for rehospitalization. They are also trained to develop a multidisciplinary care plan to address identified needs. Results One hundred and twenty eight medical students at the Emory University School of Medicine received the curriculum during their required 4-week ambulatory rotation. Following the course, 72% responded positively ("agree" or "strongly agree") to their ability to structure the postdischarge visit. Only 15% responded positively prior to the course. 72% responded positively to their ability to develop a multidisciplinary care plan versus 40% prior to the course. Medical students' confidence and attitude scores relating to care transitions improved significantly after participation in the curriculum. Overall, 92.5% of participants expressed satisfaction with the curriculum. Discussion The transfer of patient care from the hospital team to healthcare providers in the community is a high-risk process characterized by fragmented, nonstandardized care. This resource educates medical students on the critical role of the receiving outpatient physician/ interprofessional team in care coordination and safety promotion during care transitions.